A Platform Service Supply Chain: Interaction Between AI Strategy Adoption and Pricing Mechanism Selection - Xiaodong Wang; Zhao Zhu; Pengfei Ma (Discrete Dynamics in Nature and Society)
In the operation of service-sharing platforms, artificial intelligence (AI) strategy may or may not be adopted, alongside different pricing mechanism. The interaction between a platform’s decision to adopt the AI strategy and pricing mechanism selection is a valuable area for research. This paper examines the implications of a platform adopting or not adopting the AI strategy, focusing on two mechanisms: service provider pricing and platform pricing. The findings indicate that when consumers have a high sensitivity to the level of intelligent services, the platform should adopt the AI strategy, which may negatively impact the profits of both service providers. Platform pricing is more beneficial for the platform and high-quality service providers, while it reduces the profits of the low-quality service provider. When consumers have a low sensitivity to the level of intelligent services, adopting the AI strategy is more advantageous for the high-quality service provider and the platform itself. In addition, when service providers determine the service prices and consumers have a high sensitivity to the level of intelligent service levels, the platform is inclined to adopt the AI strategy, which may adversely affect the profits of both service providers.